Case report: Atypical POEMS syndrome without polyneuropathy, complicated by borderline TAFRO syndrome - Tan, Shuai; Shang, Mingyue; Masaki, Yasufumi; Ni, Jing; Da, Yuwei; Sun, Jing; Cao, Yaofang; Su, Li; Sun, Wanling (Frontiers in Medicine, 2024)
This case provides valuable information for identifying POEMS syndrome, especially when EMG results of peripheral neuropathy may suggest severe edema. It also highlights a specific rare disease typeatypical POEMS syndrome without polyneuropathy.  The patient, critically ill, presented with multiple rare diseases simultaneously, including POEMS syndrome, TAFRO syndrome, and Castleman disease, offering a valuable opportunity to improve disease identification.  Rapid diagnosis and treatment (using dexamethasone) was crucial in saving the patient's life. Continued improvement in quality of life was observed with ASCT after several courses of chemotherapy using the Rd regimen, and the prognosis remains favorable to date.